Analysis of instant energy drinking products containing eurycoma longifolia / Linda Mohd Jamal - Mohd Jamal, Linda (2007)
The significant of this study is to isolate various constituents in instant drinking products claimed containing Eurycoma longifolia and then comparing the chromatogram achieved from high performance liquid chromatography (HPLC) to identify whether the samples chosen have the same shape of chromatogram or not. From this identification, a standard method can be further developed to be used in all industries related to manufacturing instant drinking products containing Eurycoma longifolia. As a result, quality control and reliability of the products available in the marketplace can be improved and consumers will face less potential adverse health effects related to Eurycoma longifolia. In order to isolate, purify and characterize or identify bioactive constituents of the instant drinking products containing Eurycoma longifolia, four major steps had been used. The first step is to isolate the constituents by extracting samples with different types of solvent which are chloroform, n-butanol and ethyl acetate. The second step is to purify the extracting samples by using thin layer chromatography (TLC). The solvents used for TLC are hexane and ethyl acetate in the ratio of 8:2 respectively. For characterization or identification of the samples, UV spectroscopy and HPLC techniques had been used. Nevertheless, the outcome of this research study did not so well because of time limitation to handle HPLC properly.